The impact of e-learning in improving self-learning skills among school students under the Corona pandemic - Ashour, Sana Muqdad (Journal of Tikrit University for Humanities, 2024)
The study aimed at the effect of e-learning in improving the self-learning skills of middle school students in Baghdad schools in Karkh first for the current academic year, 2021/2022. In order to achieve the objectives of the study, a questionnaire aimed at measuring self-learning skills was adopted by reviewing previous studies and literature that dealt with the concept of e-learning, and it consisted of 45 paragraphs and distributed over four areas, and since the tool was adopted and built in 2018 and presented It was on arbitrators and had a high agreement rate and was subject to the laws of honesty and stability, so it is ready to be applied to the research sample directly. As for the research sample, it consisted of female teachers and students of the middle school in Baghdad Karkh first schools, where the results of the study indicated that there is a statistically significant effect of teaching using e-learning on improving the level of self-learning skills in favor of the experimental group, and there are statistically significant differences in improving the skills of self-learning. Self-learning, and there is a statistically significant effect of the interaction of gender and e-learning variables in improving self-learning skills for the benefit of the experimental group.